The regulating role of the peruvian government in authorizations for performing clinical trials. A qualitative study - Sanabria-Rojas, Hernán A. (2021)
Objectives: To explain the role of the Peruvian Government related to participation of different stakeholders influencing regulations for authorizing clinical trials (CT). Methodology: We present part of a case study corresponding to a PhD thesis performed between 2015 and 2017. We used document information and 14 semi-structured interviews with key informants were performed. We also systematized experiences related to clinical trial authorization and inspection, as well as verification of investigation sites. We also had access to publicly available information from the Peruvian National Institute of Health. The analysis was performed within epistemological and hermeneutical frameworks, and it was approved by the Ethics Committee from San Fernando Public Medicine School. Results: Issues identified were as follows: Delay in regulatory times authorized for CTs; suspension of authorizations for performing CTs in children, which led to progressive reduction in requests and consequently to a reduction in CTs from 2009 on. Conclusions: According to this study, regulations by Peruvian authorities have weakened, since participants and some stakeholders are not able to exert their rights, particularly with respect to competence generation for researchers when trying to develop CTs.